Children’s self-reported discomfort of restorative treatments for deep caries lesions in primary teeth: Results from a randomized clinical trial (Research, Society and Development, 2021)
The aim of this study was to evaluate the impact of different restorative techniques to treat deep caries lesions of primary molars on children’s self-reported discomfort. A randomized clinical trial with two parallel arms (1:1) was conducted in São Paulo, Brazil. 4-8 years-old children with at least one occlusal or occlusoproximal deep caries lesion in primary molars were selected. Molars were randomly allocated into two groups: (1) restoration performed with calcium hydroxide cement followed by high-viscosity Glass Ionomer Cement (CHC+HVGIC), and (2) HVGIC restoration. Immediately after the intervention, children reported the experienced discomfort during restoration to an external examiner using a Wong-Baker face-scale. Children’s self-reported discomfort was analyzed using Poisson regression comparing both groups and assessing other variables’ influence (α=5%). One hundred and eight children fulfilled the eligibility criteria and were randomized in the two groups (n=54). Most of the children who received CHC+HVGIC restorations reported none or minimal discomfort (83.3%). Similar scores (92.6%) were reported for those treated with HVGIC (p=0.758). The mean reported discomfort in children with CHC+HVGIC restorations was 0.37(1.01), and 0.41(1.01) for those with HVGIC restorations. Children’s self-reported discomfort was associated with age, sex, children’s cooperation, and intervention duration. We can conclude that CHC+HVGIC or HVGIC restorations result in none or minimal discomfort in the management of deep caries lesions, being considered a reliable option.